Diabetes and Lung Disease: An Underestimated Relationship (The Review of Diabetic Studies, 2019)
BACKGROUND: Diabetes mellitus is a systemic disorder associated with inflammation and oxidative stress which may target many organs such as the kidney, retina, and the vascular system. The pathophysiology, mechanisms, and consequences of diabetes on these organs have been studied widely. However, no work has been done on the concept of the lung as a target organ for diabetes and its implications for lung diseases. AIM: In this review, we aimed to investigate the effects of diabetes and hypoglycemic agent on lung diseases, including asthma, chronic obstructive pulmonary disease (COPD), idiopathic pulmonary fibrosis, pulmonary hypertension, and lung cancer. We also reviewed the potential mechanisms by which these effects may affect lung disease patients. RESULTS: Our results suggest that diabetes can affect the severity and clinical course of several lung diseases. CONCLUSIONS: Although the diabetes-lung association is epidemiologically and clinically well-established, especially in asthma, the underlying mechanism and pathophysiology are not been fully understood. Several mechanisms have been suggested, mainly associated with the proinflammatory and proliferative properties of diabetes, but also in relation to micro- and macrovascular effects of diabetes on the pulmonary vasculature. Also, hypoglycemic drugs may influence lung diseases in different ways. For example, metformin was considered a potential therapeutic agent in lung diseases, while insulin was shown to exacerbate lung diseases; this suggests that their effects extend beyond their hypoglycemic properties.